Developing an English Teaching Module through Deep Learning and Socio-Culturally Responsive Differentiated Instruction: An ADDIE-Based Study - Muhamad Yahrif; Suharti Siradjuddin (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study aimed to develop an English teaching module integrating deep-learning principles with socio-culturally responsive differentiated instruction for junior high school English teachers. The study employed a research and development design using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The analysis stage examined teachers’ and students’ needs and challenges in implementing differentiated English learning in the participating schools. The module was designed and developed through expert validation and iterative revision. The implementation and evaluation stages were conducted in two junior high schools in Soppeng Regency, Indonesia, involving 4 English teachers, 2 headmasters, 2 supervisors, and 150 students. Expert validation produced an overall score of 97.83%, while the implementation evaluation produced an overall score of 99.5% based on the verified scoring procedure. Student evaluation showed that 77% of respondents were very satisfied and 17% were satisfied with the instructional delivery, representing 94% positive responses. The findings indicate that the developed module demonstrated favorable [verified dimensions] and was positively received by participating users. The study contributes a context-sensitive English teaching module that integrates deep-learning principles, differentiated instruction, and sociocultural contextualization. Further research involving larger samples and comparative or experimental designs is needed to determine whether the module produces measurable effects on students’ English learning outcomes